New biflavonoids from Iresine diffusa - Suárez, Alírica I. (Revista de la Facultad de Farmacia, 2022)
Three new methoxylated and unsymmetrical biflavonoids with: a flavone-flavanone structure, diffusanone A (1), flavonol-isoflavone, diffusanone B (2), 3-methoxylated-flavonol-flavone, diffusanone C (3) had been isolated from a dichloromethane fraction of Iresine diffusa Humb. & Bonpl. ex Willd. leaves, a plant with recognized medicinal properties. The structures of the new compounds were established based on extensive spectroscopic experiments of 1D and 2D NMR, IR, and mass spectrometry. This is the first report of biflavonoids in Iresine genus.